Manajemen Program Ekstrakulikuler dalam Meningkatkan Prestasi Non Akademik Siswa di Madrasah Tsanawiyah - Indah Rizqiyatul Wasi'ah; Imam Turmudzi; Sarwan Sarwan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This study aims to analyze the management of extracurricular programs in improving students' non-academic achievement at Madrasah Tsanawiyah Negeri 1 Situbondo. The method used is qualitative descriptive, with data collection through interviews, observations, and documentation. The results of the study show that extracurricular program management includes planning, organizing, implementing, supervising, and evaluating. Planning is carried out through work meetings that discuss the types of extracurriculars, the selection of coaches, and the provision of adequate facilities and infrastructure. The organization is aimed at dividing tasks according to the competence of each coach and scheduling extracurricular activities. The implementation of the program is carried out consistently in accordance with the plan that has been prepared.In addition, supervision is carried out by the head of the madrasah and the supervisor to ensure that each activity runs according to the schedule and achieves the expected goals. Evaluations are conducted at the end of each semester to assess the effectiveness of the program, including the analysis of facilities and infrastructure, the number of meetings, and the achievement of student achievement in various non-academic competitions. The study concluded that effective management in extracurricular programs contributes significantly to the improvement of students' non-academic achievement, which in turn improves the reputation of the madrasah. Recommendations for continuous improvement in extracurricular management are recommended so that students' potential can be maximized and broader educational goals can be achieved.